The mediating role of motorcycle riding behavior in the relationship between risky riding intention and safety incidents among housewife motorcyclists in Jabodetabek - Freza Dwi Agustiani; Dian Kemala Putri (OPSI, 2026)
Motorcycles accounted for 73% of all accidents in 2024, with human mistake causing 95% of these crashes. While the experiences of female riders, particularly suburban housewife motorcyclists, who face severe multitasking demands and time constraints remain largely unexplored, little is known about how dangerous driving intentions convert into driving habits that could lead to safety problems. In order to assess how psychological variables are reflected in driving behavior and how this behavior affects safety incidents, this study utilizes the MRBQ (Motorcycle Rider Behavior Questionnaire) and PLS-SEM (Partial Least Squares Structural Equation Modeling). The findings indicate that all aspects of the MRBQ (speeding, traffic infractions, control errors, and stunts) are directly affected by risky riding intentions. It was discovered that only speed violations had a substantial indirect impact of risky riding intention on safety incidents. Speed violations is a mediator between risky riding intention and safety incidents, even though risk-taking driving intentions affect a variety of driving behaviors. Practical insights into the creation of speed management measures and psychologically grounded road safety interventions that aim to reduce safety-related events among female motorcyclists in Indonesia's urban areas are provided by the findings.